Comparison of force measurement techniques in a short duration hypersonic facility - Hyslop, A; Doherty, LJ; McGilvray, M (Springer, 2024)
Force measurement experiments have been conducted within the University of Oxford’s High Density Tunnel with a (Formula presented.) half-angle cone. The purpose of the study was to provide a direct comparison between two independent force techniques in the same facility at the same free-stream conditions to provide a quantitative and qualitative discussion of the advantages and disadvantages of both techniques. The first force measurement technique used a conventional 4-axis sting-mounted force balance which was calibrated both statically and through the stress wave deconvolution method, whilst the second technique used the less established static free-flight methodology. Experiments were conducted at a Mach 5 test condition which provided sufficient dynamic pressure to generate aerodynamic forces suitable for the measurement range of the force balance. Results for lift, drag and pitching moment coefficients were obtained over a range of angles of attack and compared with predictions from a hypersonic panel method code. Agreement between the independent force techniques and numerical data sets was good over the range of angles of attack. Maximum uncertainties were shown to be 38.46 ± 0.56 N and 22.52 ± 0.44 N for free-flight in lift and drag, respectively, and 38.74 ± 1.59 N and 22.13 ± 1.27 N for the dynamically calibrated force balance which demonstrates the superiority of free-flight.